2011
DOI: 10.1007/s00540-011-1106-7
|View full text |Cite
|
Sign up to set email alerts
|

One-lung ventilation in a patient with stenting for tracheobronchial stenosis caused by esophageal cancer

Abstract: We have provided general anesthesia for a 53-year-old man scheduled to undergo lymph node removal for right mediastinal lymph node metastases caused by esophageal cancer. One year prior, acute respiratory failure occurred because of stenosis of the carinal bifurcation resulting from advanced esophageal cancer with tracheal invasion. The patient underwent placement of tracheobronchial stents (Spiral Z Stent) in two locations (left main bronchus and trachea/right main bronchus), followed by radiotherapy and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Many reports have shown that surgical stress inhibition is mainly due to T lymphocyte-mediated cellular immunity, which also has a direct impact on the incidence of postoperative infection and tumor metastasis [16,17]. A good anesthetic method can reduce the perioperative stress response of patients and protect their immune function [17][18][19][20][21]. Because the degree of cellular immunosuppression during the perioperative period is mainly affected by the size and time of surgical trauma of patients, thoracotomy poses a greater impact on the patient's respiratory and circulatory system [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that surgical stress inhibition is mainly due to T lymphocyte-mediated cellular immunity, which also has a direct impact on the incidence of postoperative infection and tumor metastasis [16,17]. A good anesthetic method can reduce the perioperative stress response of patients and protect their immune function [17][18][19][20][21]. Because the degree of cellular immunosuppression during the perioperative period is mainly affected by the size and time of surgical trauma of patients, thoracotomy poses a greater impact on the patient's respiratory and circulatory system [22].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, information on endof-life care issues in their patient population and mode of MV, such as single lung versus double lung, pressure cycled versus volume cycled, and standard versus high-frequency ventilation, would have addressed some practical issues for clinicians and intensivist. 5 We believe that further clinical studies will provide more understanding of the role of RT in MAO requiring MV. This study has indeed paved the way to this understanding and we would like to commend the authors for this work.…”
mentioning
confidence: 92%
“…Although the double lumen endotracheal tube is the first choice in one‐lung ventilation, there are certain cases when intubation with a double‐lumen endotracheal tube is not possible. In those cases, bronchial blockers are ideal devices [24].…”
Section: Introductionmentioning
confidence: 99%